Study on the Model of Slider-crank Mechanism with Clearance based on Parameter Identification Method - Zeng Qingsheng; Wang Xiangjiang; Tang Xiaohuan (Jixie chuandong)
In order to solve the problem of the clearance on the slider-crank mechanism and improve the position precision of the slider-crank mechanism. Starting from the simple mechanism of slider-crank mechanism,the simplified model is established. By using the sensor to measure the movement parameters of artifacts of the slider-crank mechanism,then system parameters of the slider-crank mechanism are identified by using the method of parameter identification. Finally,the model of the slider-crank mechanism with clearance is established and the simulation analysis is carried out. The comparison results show that the model of using the method of parameter identification has high accuracy and modeling process is simple,a new train of thought for complex nonlinear modeling of the electromechanical system is provided.